Застосування FD-методу до розв'язання задачі Штурма – Ліувілля з коефіцієнтами спеціального вигляду - Клименко, Я.В.; Макаров, В.Л. (Український математичний журнал, 2007)
Функционально-дискретный (FD-) метод применен к решению задачи Штурма - Лиувилля с коэффициентами специального вида и получены оценки точности. Проведен численный эксперимент с помощью пакета Maple-10. We use the functional-discrete method for the solution of the Strum-Liouville problem with coefficients of a special form and obtain the estimates of accuracy. The numerical experiment is performed by using the Maple-10 software package.